Diversification strategies and the emergence of a new industrial value-chain: Challenges and opportunities for companies - Sousa, C.; Fontes, M.; Conceição, O. (Proceedings of the 18th European Conference on Innovation and Entrepreneurship (ECIE 2023), 2023)
Marine renewable energy technologies (MRET) can contribute to the decarbonization of energy, as well as to the revitalisation of other sectors, but are still an emerging and uncertain area. The development of these technologies entails the construction of a new industrial value chain, requiring the involvement of established firms from a variety of industries. Thus, it is important to understand how established firms can be mobilised to support MRET development, by pursuing diversification strategies. This paper addresses this question by looking at the case of Portuguese firms that expressed willingness to engage with MRET and investigating how they perceive the opportunities for diversification into the new business area, the changes they may need to introduce in their resources and capabilities to exploit those opportunities, and the obstacles they expect to face.